Intravenous treprostinil infusion via a fully implantable pump for pulmonary arterial hypertension - Ewert, Ralf; Grünig, Ekkehard (Clinical research in cardiology, 2017)
ObjectivesParenteral prostanoids infused via external pumps are well-established pulmonary arterial hypertension (PAH) treatments. However, local side-effects and systemic infections restrict their use. The purpose of this study was to investigate the safety of a fully implantable treprostinil infusion pump (LENUS Pro®) in patients with PAH.MethodsThirty patients with PAH undergoing pump implantation (with stable PAH therapy for ≥3 weeks pre-implantation) were included in this prospective, multicenter, observational study (NCT01979822). Primary endpoints were predefined adverse events (AEs) during implantation, in-hospital and/or during 6-month follow-up. Refill-related AEs were a secondary endpoint.ResultsTwenty-nine patients completed 6-month follow-up (one underwent lung transplantation). During implantation, one pneumothorax (not requiring drainage) occurred. Four patients had an in-hospital AE (including one catheter revision). During 6-month follow-up, AEs were most frequent at the first refill (10); the most common AE was seroma around the pump. No infections occurred. One pump required replacement because of a defective septum caused by use of a non-approved refill needle (associated with extravasation). Apart from the extravasation, no refill-related AEs were recorded. Post hoc efficacy analyses showed significant improvements in functional class [number in functional class I/II/III/IV: 0/5/21/2 (baseline) versus 3/8/17/0 (6 months); p = 0.012] and 6-min walk distance (mean ± standard deviation: 407 ± 122 m versus 445 ± 127 m; n = 17; p = 0.014).ConclusionsThis study supports use of a fully implantable treprostinil infusion pump in patients with PAH requiring parenteral prostanoids. Refills should be performed by specialized healthcare professionals at patients’ homes or at experienced centers using approved equipment.